Time-Course Changes of Serum Keratin Concentrations after Liver Transplantation: Contrasting Results of Keratin-18 and Keratin-19 Fragments - Cristina Macía; Jose Loureiro; Isabel Campos-Varela; Ihab Abdulkader; Esteban Otero; Evaristo Varo; Santiago Tomé; Arturo Gonzalez-Quintela (Case Reports in Hepatology)
Objective. Under normal conditions, adult hepatocytes express only keratin-8 (K8) and keratin-18 (K18), whereas cholangiocytes also express K19. In this study, we delineate the pattern of normal time-course changes in serum K19 and K18 levels after liver transplantation. Patients and Methods. Serum levels of the K19 fragment CYFRA 21-1 and the K18 fragments tissue polypeptide specific antigen (TPS) and M30 (a neoepitope that is generated after caspase cleavage during apoptosis) were measured at baseline and at regular intervals (up to 6 months) after liver transplantation in 11 adult patients. Results. There was a gradual decrease in serum K19 concentrations from baseline values after transplantation, following a time-course pattern similar to that of serum bilirubin. In contrast, serum concentrations of K18 fragments increased markedly shortly after transplantation and gradually decreased thereafter, following a time-course pattern similar to that of serum transaminases. The increase in TPS tended to occur earlier than that in M30, suggesting an initial predominance of hepatocyte necrosis followed by a predominance of apoptosis in the first days after transplantation. Five patients presented posttransplant complications (acute rejection in three cases and HCV recurrence in two cases). An early increase in serum K19 concentrations was observed in all cases. An increase in serum concentrations of K18 fragments (M30 and TPS) was observed in the two cases with HCV recurrence and was more variable in the three cases with acute rejection. Conclusions. Serum concentrations of K19 and K18 fragments follow a dissimilar pattern of time-course changes after liver transplantation. The diagnostic value of variations in these normal patterns should be addressed in future studies.